An epidemiological study of type-2 diabetes mellitus among adults of 30 years and above in urban Meerut - Kanaujia, Anglica; Kumar, Arun; Jain, Seema; Singh, Ganesh; Mittal, Chhaya (International Journal Of Community Medicine And Public Health, 2021)
Background: Diabetes mellitus (DM) comprises a group of metabolic disorders that share the common feature of hyperglycemia. Type 2 diabetes accounts for over 90-95% of all people with diabetes. Aim and objectives of the study was to know the prevalence of diabetes mellitus and associated risk in an urban population of Meerut. Methods: The present study was conducted in the field practice area of Urban Health Training Centre, LLRM Medical College, Meerut by house to house survey among adults 30 years and above. Results: Prevalence of DM in the present study was found to be 13.1%. Among the total diabetics, 10% were known diabetics 3.1% were newly diagnosed diabetics. Socio-demographic factors associated with diabetes are age, socio-economic status, educational status and marital status while factors such as gender, religion, caste and type of family were found to be statistically insignificant. Conclusions: Risk factors like family history, hypertension and behavioural factors like alcohol consumption and smoking were associated with diabetes prevalence.